Conceptual bases of building ACS with complex energy objects - Дуэль, Михаил Александрович; Канюк, Геннадий Иванович; Фурсова, Татьяна Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The possibility of using modern advances of automatic control theory and information technology are considered for the rehabilitation of exploited and building a new ACS multilevel, multifunction and fully-variable control objects